Production of Thermoplastic Composites reinforced with Posidonia Oceanica Fibers - Slimani, Faouzi; Ghanmi, Ines; Ghanmi, Samir; Guedri , Mohamed (Engineering, Technology & Applied Science Research, 2024)
This study investigates the development and characterization of a new biocomposite and biodegradable material based on natural fibers. This new biocomposite is composed of commercially available biodegradable polylactic acid (PLA) as a matrix and Posidonia Oceanica (PO) fibers collected from the coasts of Tunisia as reinforcement. This new material is produced by heating and pressing the two components in a special device. The use of PO, or sea balls, will allow exploiting one of the marine residues abundant on Tunisian beaches, instead of exploited industrially, and to preserve the beaches from debris given the impact of tourist activity in the Tunisian economy. The PLA/PO coupling allowed obtaining a biocomposite with promising mechanical properties. The improvement in maximum stress and strain after the addition of PO is one of the highlights of the results of this work.